KESEHATAN KERJA PEMAKAI BIKE LIFT BUATAN PADA BENGKEL SEPEDA MOTOR KONVENSIONAL DI KOTAMADYA PADANG - , Amrizal Arief, Drs.,M.Kes., Prof. Dr. dr. Soebijanto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Nowadays the motorcycle maintenance is conducted by the workers either those who work in the formal workshop or in the informal sectors. The formal workshop workers with the standard-working attitude, but the informal sector workshop workers with the sitted-working attitude. The standard-working attitude as well as the sitted-working attitude are called the static attitudes, which do not fulfill the healthy working rules. so that the negative health effects such as weight loss, muscle strength, heart palpitations and lactic acid. Is there any difference of the alternative increase for the workers who work with the sitting position, applying the ergonomics concept in the working facility, making the made-up bike-lift with the controlling height, and changing the woring position from static to the dynamic one. It means the worker works with the standing or sitting position with the help of the working seat. The made up bike-lift is far cheaper in price, operational, and maintenance compared to the bike-lift in the formal garage. The Objective of the Study: to repair the static working attitudes with the sittedstandard working attitudes is used motorcycle bike lift by using a lifted stool. Is there a progress towards the working health after the change of the working attitudes from the static to the dynamic one? Methods of the Research: the quasi-experimental method with the Pretest-Posttest Equivalent-Group Design. The research place was the conventional at 2 Herkules Street, Tunggul Hitam, Padang City. The subjects were determined by the inclusion criteria: 16 conventional workshop workers, whereas the controlled subjects were 16 Main Dealer Honda C. Hayati workers, at 35 Pemuda Street, Padang. The research free variables was working with the sit stand working attitude and the stand working attitude. The research bound variables consisted of the weight weighed in Digital Camry, the hand muscle power measured by the dynamometer, the working burden with the nerve-pulse indicator measured by the Personal ECG Recorder EP-202 ©, the fatigue with the blood lactate acid measured by Accutrend ® Lactate. The statistic analysis used to see the differences among the 4 variables with the different attitudes was the Covariance Analysis, while the differences among them were measured by using independent t-test The Result of the Research: 1. There are differences in body weight between worker job attitudes dynamic andmechanical standard working attitude with p <0.05, independent samples t test statisticaldifference in weight between these two showed differences in work attitudes, work attitudessit stand 0.3506 ± 0.13582, work attitude stood 0.7950 ± 0.22862. 2. There are differences in muscle strength between the work attitudes of workers sit up and work attitudes of workers standing with p <0.05, independent samples t test statistical difference betweenthe two muscle strength showed differences in work attitude, work attitude sitting stood 1.7369 ± 1.60029, attitude employment stood 4.5206 ± 2.46114. 3. There are differences in heart rate between worker job attitudes and worker sitting standing. standing working posture with p <0.05, independent samples t test statistical difference between the two heart rate work attitude shows the difference, working posture sitting standing -23.5356 ±6.50793, standing job attitude -27.9169 ± 5.33915. 4. There is a difference in fatigue between work attitudes of workers sit up and mechanical work attitude stood with p <0.05, independent samples t test statistical difference in fatigue between two attitudes, show differences, dynamic work attitude -0.2175 ± 0.50317, the standard work attitude -1.4525 ±0.29117. Conclusion:This study proves that the work attitude sitting up, in terms of weight change variables, hand muscle strength, work load, and muscle fatigue, better than standing working posture. Therefore suggested, in working with working attitude should sit stand.